Reproductive Cycle of Marphysa sanguinea (Montagu, 1815) (Polychaeta: Eunicidae) in the Lagoon of Tunis - Monia El Barhoumi; Patrick Scaps; Fathia Zghal (The Scientific World Journal)
The reproductive cycle of Marphysa sanguinea (Polychaeta: Eunicidae) was studied in the Lagoon of Tunis between May 2006 and May 2007. M. sanguinea is a gonochoric species. There were no morphological differences between males and females, and spawning occurred without epitokal metamorphosis. Gonads are not well defined in either sex. The process of spermatogenesis takes place in the coelomic cavity. Mature males show all stages of spermiogenesis at any one time. The ovaries of M. sanguinea consist of coelomic germ-cell clusters surrounded by a thin envelope of follicle cells derived from the peritoneum. Germ cells in premeiotic and previtellogenic phases are observed in one cluster. In each cluster the more differentiated oocytes detach and float free in the coelomic cavity where they undergo vitellogenesis as solitary cells. The cytoplasmic material of the mature oocytes (diameter superior to 200 μm) is asymmetrically distributed; large lipid droplets and large yolk spheres occupy the vegetal pole of the oocyte while smaller yolk spheres are situated in the animal hemisphere. The female coelomic puncture has a heterogeneous aspect and shows different oocyte diameters. The reproductive period is more intense in winter period from January to March. Spawning occurs mainly in April.